EFFECT OF ADDING TWO DIFFERENT CONCENTRATION OF ORGANIC CHROMIUM ON PERFORMANCE OF THREE BROILER STRAINS: Faris A. AL-Obaidi , Khalid A. AL -Soudi and Amer A. Rashed - AL-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2006)
This study was carried out to determined the effect of adding 0,150,200 ppbof organic chromium in feed on dressing percentages and meat composition of three commercial broiler strains (Lohman ,Ross and Hubbard) .A total of 450day old chicks (150 chicks per strain)were distributed into nine treatments and each treatmentDivided into two replicates (25 birds per replicate) .The data obtained reveald the following results:Adding 150 and 300 ppb organic chromium increased significantly ( P<0.05) dressing percentages with or without giblets , and no significant differences appeared in edible organs percentages includes liver, heart and gizzard , also adding 150 or 300 ppb of organic chromium increased meat production through the significant (P<0.05 ) increase of primary carcass cuts which were breast and legs ,also increased significantly(P<0.05) protein , carbohydrates and decreasedsignificantly(P<0.05) lipids, and moisture in these cuts meat. No significant differences appeared for the interaction between adding chromium and genetic factors for the three broiler strains in dressing percentages and meat composition and the effect was significant (P<0.05) incarcass cuts except legs percentages .